Philosophies of the sciences : a guide - Allhoff, Fritz (Wiley-Blackwell, 2010)
A collection of essays discussing a wide range of sciences and the central philosophical issues associated with them, presenting the sciences collectively to encourage a greater understanding of their associative theoretical foundations, as well as their relationships to each other